The New Spirit of Capitalism, Innovation Fetishism and New Information and Communication Technologies - Ampuja, Marko (Javnost-The Public, 2016)
The neoliberal developments over the past 30 years have received much support from a set of ideas that can be defined as “the new spirit of capitalism”. These ideas have offered powerful legitimisations of neoliberalism, conceived as a progressive force that has replaced the supposedly bureaucratic structures of earlier Keynesian welfare states with market-driven network structures that allow innovations, creativity and entrepreneurship to flourish. In this article, I will critically examine the constituents of the new spirit of capitalism, in particular its intimate association with liberal discourses of innovation. I will then focus on how such ideas have come forward in recent information society thinking via a discussion of Manuel Castells's influential network society theory. This is followed by a critique of mainstream understandings of innovation from a neo-Marxist perspective, with an eye towards new information and communication technology and critical media research in times of a growing contestation of neoliberal hegemony.